Israel : Technical Assistance Report- Consultations on the Work of the Banking Supervision Department of the Bank of Israel. (IMF Staff Country Reports; Country Report ;, 2016)
This paper first takes a historical perspective, studying the implications of the oil boom of the 2000s on industry structure and economy-wide productivity. It then examines progress with the ongoing transition thus far both in the real sector and in the labor market, bearing in mind the short time span that has passed. This paper also explores two possible explanations for lagging productivity-namely, product market regulation and the low level of research and innovation. An extensive data set of mainland Norwegian firms is used to empirically assess the potential productivity gains from product market reforms as well as increasing research and development spending.